Analisis Pengaruh Merek dan Negara Asal (Country Of Origin) Terhadap Sikap Konsumen Dalam Memilih Produk Handphone (Studi Kasus Pada Mahasiswa S1 Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta) - Armi, Muhammad Reza Syaiful; , Drs. Sujadi, M.M (2015)
This study aims to investigate the influence of brand and country of origin on consumer attitude in selecting mobile products. And to determine which variables are most influential on consumer attitudes in selecting mobile products. The analysis tool used is multiple linear regression, by retrieving data using interviews in respondents Faculty of Economics and Business, University of Muhammadiyah Surakarta class of 2011 to 2014. This study refers to the positive approach, the approach that started the research with the hypothesis and then followed by hypothesis testing. From the analysis ofeach variable can be seen that the variable of brand and country of origin (country of origin) significantly influence consumer attitudes in choosing a mobile phone. And the results of the study also showed that variable home country (country of origin) has the strongest influence on consumer attitudes variables. It can be seen from the value of the smallest probability level compared to branded variable that is equal to 0,010, or 1%. This means that in line with the research Bambang Pujadi (2010), Sarwo Edi (2013, and Dedi Mulyadi, et al (2012) which states that the brand influence on consumer attitudes, and research conducted by Leoni and Fajrianthi Rizki (2012), Rahmawat Setyanigsih, et al (2007), and Magyar Slamet Permana (2013) which states that the country of origin (country of origin) effect on consumer attitudes. It is expected the mobile phone manufacturers really pay attention to all matters relating to the brand and country of origin in order to influence the views and attitudes of consumers in selecting mobile products and other factors that affect consumer attitude in selecting mobile products.